2012
DOI: 10.1051/0004-6361/201116774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular clouds under the influence of massive stars in the Galactic Hii region G353.2+0.9

Abstract: Aims. We investigate the structure of the Galactic Hii region G353.2+0.9, by analyzing (sub-)mm molecular-line and -continuum observations. This region is excited by the massive open cluster Pismis-24. We study the detailed morphology, distribution, and physical parameters (column and volume densities, masses, temperatures and opacities) of the molecular gas and dust. We are also interested in the variation in these parameters across the photon-dominated region. Methods. We observed various molecules and trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…8 and Table 5) represent real substructures or are rather the effect of variable extinction. Although the bulk of molecular gas lies in the SofI northern field, a few molecular clumps have been found projected towards the core (e.g., CO clumps E, F, and G of Massi et al 1997, and CS clump D3 of Giannetti et al 2012). However, some of these clumps appear red-shifted and those authors suggested that this is because these may lie in the rear part of the complex, accelerated away by rocket effect.…”
Section: Star Formation On the Smaller Scale: Substructures In Pismis 24mentioning
confidence: 97%
See 1 more Smart Citation
“…8 and Table 5) represent real substructures or are rather the effect of variable extinction. Although the bulk of molecular gas lies in the SofI northern field, a few molecular clumps have been found projected towards the core (e.g., CO clumps E, F, and G of Massi et al 1997, and CS clump D3 of Giannetti et al 2012). However, some of these clumps appear red-shifted and those authors suggested that this is because these may lie in the rear part of the complex, accelerated away by rocket effect.…”
Section: Star Formation On the Smaller Scale: Substructures In Pismis 24mentioning
confidence: 97%
“…As discussed in Appendix F, this region hosts less massive stars than subcluster core C which may be an effect of photo-ionisation (Dale et al 2012b). Giannetti et al (2012) found that many of the gas clumps in the north are virialised and/or exhibit possible compression from outside, which may lead to further star formation.…”
Section: Star Formation On the Smaller Scale: From Gas To Starsmentioning
confidence: 99%
“…For CS, there is a large scatter in observed values for highmass star-forming regions with [CS]/[H 2 ] = 10 −9 to a few times 10 −10 (Gianetti et al 2012;Li et al 2015;Neufeld et al 2015). Low-mass cores have typical values of a few times 10 −9 (e.g.…”
Section: The Pdfs From Cs and N 2 H +mentioning
confidence: 99%
“…A shell of fragmented molecular gas was also identified in CO emission (e.g. Massi et al 1997) and Giannetti et al (2012) show the presence of a velocity gradient in the region suggesting that the expansion of the ionised gas is pushing the molecular gas. In addition, at least four other H II regions (see Fig.…”
Section: Introductionmentioning
confidence: 92%